Quantitative Ethnobotany of Medicinal Plants Used by Indigenous Communities in the Bandarban District of Bangladesh - Faruque, Mohammad O.; Uddin, Shaikh B.; Barlow, James W.; Hu, Sheng; Dong, Shuang; Cai, Qian; Li, Xiaohua; Hu, Xuebo (Frontiers in Pharmacology, 2018)
This study documents information on significant ethnomedicinal plants, which was collected from the traditional healers of three indigenous communities of Bangladesh. The documented data were quantitatively analyzed for the first time in this area. The information was obtained through open-ended, semi-structured questionnaires. The benefits, importance and coverage of ethnomedicine were expressed through several quantitative indices including Informant Consensus Factor (ICF), Use Value (UV), Frequency of Citation (FC), Relative Frequency of Citation (RFC) and Relative Importance Index (RI). The agreement of homogeneity between the present and previous studies and among the indigenous communities was evaluated using the Jaccard Index (JI). A total of 159 ethnomedicinal plant species, which were distributed in 132 genera under 62 families, were documented from 174 informants. Of these, 128 plants were native and 31 were exotic. Of a majority of documented species, herbs and leaves were the most utilized plant parts for the preparation of ethnomedicines (45.28%) whereas pastes (63.03%) were the most popular formulations. Among the documented species, the dominant families were the Asteraceae (14 species) and the Lamiaceae (12 species). The highest ICF value was 0.77 for digestive system disorders. Based on UVs, the five most commonly used ethnomedicinal plant species in the study area were Duabanga grandiflora (0.43), Zingiber officinale (0.41), Congea tomentosa (0.40), Matricaria chamomilla (0.33) and Engelhardtia spicata (0.28). The highest RFC was recorded for Rauvolfia serpentina (0.25). The highest RI value was calculated for both Scoparia dulcis and Leucas aspera (0.83). Importantly, 16 species were reported with new therapeutic uses and to our knowledge, 7 species described herein have never been ethnobotanically and pharmacologically studied, viz: Agastache urticifolia, Asarum cordifolium, Congea tomentosa, Engelhardtia spicata, Hypserpa nitida, Merremia vitifolia and Smilax odoratissima. The present study showed that traditional treatment using medicinal plants is still widespread in the study area. Documentation of new ethnomedicinal species with their therapeutic uses shall promote further phytochemical and pharmacological investigations and possibly, lead to the development of new drugs.